2019
DOI: 10.1016/j.exer.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Fixation instability during binocular viewing in anisometropic and strabismic children

Abstract: Fixation instability and vergence instability during binocular viewing suggests that discordant binocular visual experience during childhood, especially strabismus, interferes with ocular motor development. Amblyopia adds to instability of the nonpreferred eye. Vergence instability may limit potential for recovery of binocular vision in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 41 publications
2
49
1
Order By: Relevance
“…4,6,13,18,19 However, smaller angles of deviation and preserved binocular function may lessen instability. 13 Unpublished monocular viewing data from the cohort described by Kelly et al 20 also show amblyopic and nonamblyopic children with strabismus and/or anisometropia have larger fellow eye instability than controls (Figure 1).…”
Section: Fixation Instabilitymentioning
confidence: 89%
See 1 more Smart Citation
“…4,6,13,18,19 However, smaller angles of deviation and preserved binocular function may lessen instability. 13 Unpublished monocular viewing data from the cohort described by Kelly et al 20 also show amblyopic and nonamblyopic children with strabismus and/or anisometropia have larger fellow eye instability than controls (Figure 1).…”
Section: Fixation Instabilitymentioning
confidence: 89%
“…8 Vergence instability has been reported while viewing with two eyes in adults with large angle exotropia, suggesting an association of suppression with disconjugate eye movements. 6 Recently, Kelly et al 20 reported increased fixation instability and vergence instability, regardless of current amblyopia, in strabismic and anisometropic children compared with controls ( Figure 2). Fellow eye instability was not associated with amblyopic eye visual acuity or stereoacuity.…”
Section: Fixation Instabilitymentioning
confidence: 95%
“…7 Methods of retinal videographic analysis of fixation instability were not available for this study. 8,9…”
Section: Methodsmentioning
confidence: 99%
“…22,26 Furthermore, anisometropic amblyopia is associated with greater fixation stability. 27 In strabismic amblyopia on the other hand, there is often no measurable stereoacuity, even if visual acuity has improved after treatment. 22,28 However, contrast sensitivity is more likely to be preserved, 26 which might suggest that individuals with strabismic amblyopia retain better monocular spatial resolution at the expense of reduced binocularity.…”
Section: Behavioral Consequencesmentioning
confidence: 99%